Anksiozne motnje pri otrocih in mladostnikih - Dobnik Renko, Bernarda (Psihološka obzorja (Ljubljana), 2020)
Anxiety is one of the most common mental disorders in childhood and adolescence. If it is not treated, the symptoms aggravate over time and continue into adulthood. Early treatment is important, because an untreated anxiety disorder often results in lower academic efficiency, school abandonment and social isolation. Cognitive behavioural therapy is an effective method of treatment, and the main principles thereof are presented in this article.
Keywords: adolescents; anksiozne motnje; anxiety disorders; children; cognitive behavior therapy; duševne motnje; kognitivno vedenjska terapija; mental disorders; mladostniki; otroci